COVID-19 Infection Process in Italy and Spain: Are Data Talking? Evidence From ARMA and Vector Autoregression Models - Monllor, Paloma; Su, Zhenyu; Gabrielli, Laura; Taltavull de La Paz, Paloma (Frontiers in Public Health, 2020)
COVID-19 has spread successfully worldwide in a matter of weeks. After the example of China, all the affected countries are taking hard-confinement measures to control the infection and to gain some time to reduce the significant amount of cases that arrive at the hospital. Although the measures in China reduced the percentages of new cases, this is not seen in other countries that have taken similar measures, such as Italy and Spain. After the first weeks, the worry was whether or not the healthcare system would collapse rather than its response to the patient’s needs who are infected and require hospitalisation. Using China as a mirror of what could happen in our countries and with the data available, we calculated a model that forecasts the peak of the curve of infection, hospitalisation and ICU bed numbers. We aimed to review the patterns of spread of the virus in the two countries and their regions, looking for similarities that reflect the existence of a typical path in this expansive virulence and the effects of the intervention of the authorities with drastic isolation measures, to contain the outbreak. A model based on ARMA methodology and including Chinese disease pattern as a proxy, predicts the contagious pattern robustly. Based on the prediction, the hospitalisation and intensive care units (ICU) requirements were also calculated. Results suggest a reduction in the speed of contagion during April in both countries, earlier in Spain than in Italy. The forecast advanced a significant increase in the ICU units needs for Spain surpassing eight thousand units by the end of April, but for Italy, ICU needs would decrease since in the same period, according to the model. We present the following predictions to inform political leaders since they have the responsibility to maintain the national health systems away from collapsing. We are confident this data could help them into decision-taking and place the capitals (from hospital beds to human resources) into the right place